Curation décoloniale: artistes noirs à Espírito Santo - Carvalho, Mayara Simões de; Guimarães, Aissa Afonso (Farol, 2024)
The history of art was constructed with exclusive criteria that make issues of gender and race invisible. The arts, like countless other areas, are oppressive and legitimize white, European, middle-class and, above all, male artists. The movement driven by female artists from the 1960s and 1970s continues to unfold today, where it is still necessary to claim and value female artistic expressions. In this way, the selection of productions by black artists in Espirito Santo students, mothers, teachers, artists and women aims to produce and disseminate the arts. The productions shared in this article dialogue with each other, in a diversity of artistic languages, techniques and research in the artistic field. There are women, not only behind the work being represented, but women who represent themselves and present strength and sensitivity through art. The black woman is evident as a protagonist in art, affirming her presence and her struggles for equality and rights.